Identity and Commitment: Sen's Conception of the Individual - John B. Davis (Tinbergen Institute, 2004)
This paper develops a conception of personal identity for Amartya Sen's capability framework that emphasizes his self-scrutinizing aspect of the self and related concept of commitment, and compares this conception to the co1lective intentionality-based one advanced in Davis (2003c). The paper also distinguishes personal identity and social identity, and contrasts Sen's framework with recent standard economics' explanation of social identity in terms of conformity. Sen's concept of commitment is examined in two formulations, and the later version is related to Bernard Wi1liams' thinking about identity-conferring commitments. The paper concludes by arguing that explaining personal identity as a special capability and possible object of social-economic policy provides one way of resolving the debate over whether the capability framework ought to have a short-list of essential capabilities.
Keywords: D23; 330; Sen; personal identity; social identity; commitment; reflexivity; theory of conformity; collective intentionality; Bernard Williams; capabilities; Nussbaum; Verhaltensökonomik; Sozialökonomik; Sozialer Status; Theorie